Assessing the long-term effects of conditional cash transfers on human capital: evidence from Colombia (2011)
Conditional Cash Transfers (CCT) are programs under which poor families get a stipend provided they keep their children in school and take them for health checks. While there is significant evidence showing that they have positive impacts on school participation, little is known about their long-term impacts on human capital. In this paper we investigate whether cohorts of children from poor households that benefited up to nine years from Familias en Acción, a CCT in Colombia, attained more school and performed better in academic tests at the end of high school. Identification of program impacts is derived from two different strategies using matching techniques with household surveys, and regression discontinuity design using census of the poor and administrative records of the program. We show that, on average, participant children are 4 to 8 percentage points more likely than nonparticipant children to finish high school, particularly girls and beneficiaries in rural areas. Regarding long-term impact on tests scores, the analysis shows that program recipients who graduate from high school seem to perform at the same level as equally poor non-recipient graduates, even after correcting for possible selection bias when low-performing students enter school in the treatment group. Even though the positive impacts on high school graduation may improve the employment and earning prospects of participants, the lack of positive effects on the test scores raises the need to further explore policy actions to couple CCT's objective of increasing human capital with enhanced learning.